A meta‐analysis on observed paternal and maternal sensitivity. Issue 6 (29th July 2022) - Deneault, Audrey‐Ann; Cabrera, Natasha J.; Bureau, Jean‐François
Abstract: Two meta‐analyses were conducted ( N  = 10, 980 child–father dyads) with 93 studies published between 1983–2020, primarily in North America and Europe, on observed parental sensitivity to children (3–180 months; 48% girls; 14% non‐White) in partnered mothers and fathers. The first meta‐analysis found higher maternal mean levels of observed sensitivity, with a small effect size ( d  = −.27). Differences between parents were larger with micro coding and triadic/family assessments. Differences narrowed as a function of publication year and were not significant in European samples. The second meta‐analysis identified a moderate correlation between observed maternal and paternal sensitivity ( r  = .23 after adjusting for probable publication bias). Correlations were larger in Middle Eastern samples and with composite sensitivity scales.